Physiological and physicochemical behaviour of coated banana passion fruit (Passiflora mollissima Bailey) stored at two temperatures - Téllez, Claudia Patricia; Fischer, Gerhard; Quintero, Omar Camilo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
The objective of the study was to evaluate postharvest behaviour of curuba (banana passionfruit) of cultivars ‘Ruizquin 1’ (R1) and ‘Ruizquin 2’ (R2), coated with Primafresh wax (mixture of acid-fatty-sucrose esters) and then stored at 8°C (85% RH) or 20°C (53% RH) over a period of 25 and 55 days for fruits with or without coating, respectively. Fruits of all treatments showed climacteric behaviour. The climacteric peak occurred faster in fruits without coating, between 11 (R1) and 12 days (R2) at 20ºC and between 12 (R2) and 14 days (R1) at 8ºC. Coa- ted fruits had lower respiration rates and showed a climacteric peak later, at 20ºC at 31 (R1) and 30 days (R2), at 8ºC at 31 (R1) and 38 days (R2); in the latter treatment the lowest rates during the climacteric peak were registered [28.97 mg CO2·kg-1·h-1]. Coated fruits had a higher pH and total titratable acid content (TTA) than fruits without wax. The fruit fresh weight and pulp firmness were better conserved in coated fruits, while total soluble solids (TSS) content and TSS/TTA relation were higher in uncoated fruits. Only cold storage of fruits (without wax) resulted in a slower loss of weight and firmness, lower respiration rate and decay of climacteric point, an increase in TSS and ATT, lower pH, and lower TSS/TTA ratio compared to curuba stored at 20°C.